ANALISIS YURIDIS PERTANGGUNGJAWABAN PIDANA DALAM PASAL 5 UNDANG-UNDANG NOMOR 8 TAHUN 2010 TENTANG PENCEGAHAN DAN PEMBERANTASAN TINDAK PIDANA PENCUCIAN UANG - Tedi Franggoes Andri Siburian; Alvi Syahrin; Muhammad Hamdan; Sunarmi Sunarmi (USU LAW JOURNAL, 2018)
ABSTRACT The development of the money laundering problem keeps increasing from year to year, the quality of the criminal offence of money laundering is done the more organized and systematic not only threaten the stability and integrity of the financial system and economy system, but also can harm the joints of the life of society, nation, and State. This type of research is the normative legal research, namely research on principles of law that defends dotted from specific legal nomenclature field. From the results of the study known to defendant Arista Kurniasari was a suspect case of fraud and money laundering, with fictitious investment mode batik, ATK and sports top job procurement in the education service of the city of Semarang. Judge PN Semarang, declare the defendant is proven legally and convincingly guilty of committing criminal acts "concurrent some of the criminal acts of fraud, each of which stands on its own and the criminal offence of money laundering", with imprisonment for 12 year to account for his actions.   Keywords: Criminal Liability- Crime- Money Laundering